2021
DOI: 10.1186/s41065-021-00201-0
|View full text |Cite
|
Sign up to set email alerts
|

Identification and validation of hub genes of synovial tissue for patients with osteoarthritis and rheumatoid arthritis

Abstract: Background Osteoarthritis (OA) and rheumatoid arthritis (RA) were two major joint diseases with similar clinical phenotypes. This study aimed to determine the mechanistic similarities and differences between OA and RA by integrated analysis of multiple gene expression data sets. Methods Microarray data sets of OA and RA were obtained from the Gene Expression Omnibus (GEO). By integrating multiple gene data sets, specific differentially expressed ge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 48 publications
(45 reference statements)
0
13
0
Order By: Relevance
“…KEGG analysis of the target genes showed that endocytosis, salmonella infection, phagosome and ubiquitin-mediated proteolysis are involved in TMJOA. Previous studies have suggested that the biological process of ubiquitination leads to OA by regulating the expression of inflammatory cytokines ( Radwan et al, 2015 ; Ge et al, 2021 ). Zucker-Franklin (1966) showed that phagosomes participate in the regulation of synovial fluid leukocytes during RA development.…”
Section: Discussionmentioning
confidence: 99%
“…KEGG analysis of the target genes showed that endocytosis, salmonella infection, phagosome and ubiquitin-mediated proteolysis are involved in TMJOA. Previous studies have suggested that the biological process of ubiquitination leads to OA by regulating the expression of inflammatory cytokines ( Radwan et al, 2015 ; Ge et al, 2021 ). Zucker-Franklin (1966) showed that phagosomes participate in the regulation of synovial fluid leukocytes during RA development.…”
Section: Discussionmentioning
confidence: 99%
“…CIBERSORT is a deconvolution algorithm that utilizes linear support vector regression to evaluate the expression matrices of immunocellular subtypes, and now is increasingly being used for immune infiltration characterization analysis in non-tumor tissues ( Ge et al, 2021 ). Infiltration analysis of immune cells in HCC patients using RNA-Seq data can be an important guide in disease research and treatment prognosis prediction, etc.…”
Section: Methodsmentioning
confidence: 99%
“…CIBERSORT is a deconvolution technique based on the premise of linear support vector regression for immune cell subtype expression matrices, CIBERSORT was initially used for the analysis of tumor microenvironment (TME) and is now being increasingly applied in the characteristic analysis of immune infiltration in non-tumor tissues ( Ge et al, 2021 ). The synovial tissue of rheumatoid arthritis is composed of various immune and inflammatory cells, interstitial tissue, cytokines, and chemokines, which is an integrated loading system.…”
Section: Materals and Methodsmentioning
confidence: 99%